“We Hardly Have Any Moose Around Here Anymore”: Climate Change and the Barriers to Food Security in the Dehcho Region, Northwest Territories - Ross, Paulina; Mason, Courtney W. (ARCTIC, 2020)
Rural Indigenous communities across northern Canada are experiencing high rates of food insecurity as a resultof complex constraints to accessing quality market foods and engaging in local food procurement. Climate change is impacting the ability of northern Indigenous communities to acquire, access, and utilize food that is culturally relevant and sustainable. This research examines the interconnected sociocultural, political, economic, and environmental challenges related to food security in the community of Fort Providence situated in the Dehcho Region of the Northwest Territories. The objective of this research was to consult with community members to understand the impacts of climate change on local food procurement and to explore the myriad challenges related to food security. We utilized Indigenous methodologies to guide all aspects of the research. Evidence was collected using semi-structured interviews with Dene and Métis Elders, knowledgeable land-users, and other community members. Our research demonstrates that changing hydrological systems and ecosystems, unpredictable weather patterns, the presence of non-local harvesters, the loss of traditional knowledge, and the high costs of living in a rural northern community impact local food security. The results of this research can inform policies that reflect the needs of residents, address the distinct barriers to procuring local food, and provide a basis for understanding the complexities of foodsecurity in the Dehcho and other subarctic regions. Les collectivités autochtones rurales du Nord canadien connaissent des taux d’insécurité alimentaire élevés enraison de contraintes complexes en matière d’accès à des aliments du marché de qualité et d’engagement à s’approvisionner en nourriture locale. Le changement climatique a des incidences sur la capacité des collectivités autochtones du Nord à acquérir et utiliser des aliments culturellement pertinents et durables ou à y avoir accès. Cette recherche se penche sur les défis interreliés sur les plans ...